Pengaruh Laba Terhadap Likuiditas Perusahaan - Supriadi, Yoyon; Gendalasari, Gen Gen (Jurnal Ilmiah Manajemen Kesatuan, 2013)
Each company established course aims to derive a profit or benefit that can be used for the welfare of the company owners or shareholders. In every company liquidity is an important part of measuring the extent to which companies are able to pay maturing obligations to its creditors. Liquidity is a measure of investor decision-making, in which investors learn the level of liquidity and profitability in order to take the right decision for the future. Through this research are expected to know how the liquidity of the company if it is in accordance with the standard value of liquidity compared with the same company with a view of the profit, if not then impact whether and how the best solution which can be given to the company. Regression coefficient PT. Medco Energi International Tbk shows that Return On Assets (ROA) has a positive effect on the current ratio. The result of F test for the company showed no significant effect between Return On Assets (ROA) of the current ratio, this is because there are other factors that affect the current ratio. PT. Medco Energi International has a significant effect between Return On Assets (ROA) on the current ratio. Keywords : Return, Liquidity, Profit.